Effectiveness of composting as a strategy of waste management among livestock farmers in galle district - Perera, P.W.A.; Chanuthika, T.G.N.T.; Atapattu, N.S.B.M. (University of Jaffna, 2018)
Livestock waste has become an environmental issue in Sri Lanka today. A group of farmers had been given a training to utilize livestock waste for compost production by the Southern Provincial Council. Thus the present study was planned to investigate the effectiveness of composting as a livestock waste management option among the trained farmers. A structured pre-tested questionnaire was used to collect the information from 49 farmers who received training. Compost samples from all the farms which were having active compost piles were analyzed to determine the quality A comparison study was done to evaluate the knowledge on composting using all the farmers involved in composting, agriculture undergraduates who yet to study about composting and a randomly selected sample to represent the general public. Germination index was calculated for all 39 samples collected from the field. Among the farmers surveyed, 84% of famers practice composting as a source of income, whereas the rest (16%) used the compost in their home gardens. All farmers considered composting as the most effective and cheapest strategy for waste management. However, majority had a poor knowledge about moisture and temperature management as well as the maturity of compost. Awareness on the quality of compost was poor. The composting site evaluation revealed that 47.9% sites are located in sloppy lands while 27% sites located close to a wetland or a water body. According to the condition of the site location, 33% of the sites create high level impact and 45% of the sites pose middle level impact on the surrounding environment. Most of compost samples were within the standards stipulated by the SLSI. However, majority (89.7%) of compost samples had standard C:N ratios. It could be concluded that composting could be used as a strategy for livestock waste management. However further training is required to improve the quality of the final product.
Keywords: Composting; Effectiveness; End use characteristics; Livestock waste